SISTEMA DE COMUNICACIóN y CONTROL BASADO EN EL PENSAMIENTO - Román G., Avid (2019)
The present work is oriented to offer a communication via to the many people who undergo of a severe loss of function motorboat as a result of different accidents and/or diseases, so that they can control and interact better with his environment, for which an brain-computer interface has been implemented through the acquisition of EEG signals by electrodes, implementation of algorithms to extract characteristics and to execute a method of classification of such way to interpret these signals and to execute corresponding actions. The first objective to design and to construct to a System of Communication and Control Based on the Thought able to catch and to measures EEG signals. The second objective is to implement the system of data acquisition including a digital filter in real time that allows us to eliminate the noise. The third objective is to analyze the variation of the EEG signals in front of the different tasks under study and of implementing an algorithm of extraction of characteristics. The fourth objective is to work on the base of the characteristics of the EEG signals, to implement a classification system that allows to discriminate the 2 tasks under study and on the basis of it of conducting the corresponding battles.